PEMASANGAN PALATAL CRIB PADA ANAK USIA 5 TAHUN UNTUK MENGHILANGKAN KEBIASAAN MENGHISAP JARI DAN MEMPERBAIKI OKLUSI (Laporan Kasus) - Nuriyati Utami; Ismu Suharsono Suwelo (Faculty of Dentistry, Universitas Indonesia, 2015)
Finger sucking habit at child can result anterior open bite, protrusion and another malocclusion. If immediately eliminated, harder situation can be overcome immediately. Besides a psychological approach to eliminate the habit, sometimes the installation of a fixed or removable appliance is also needed. Besides eliminating finger sucking, a palatal crib attached fixed at a five years old child could so improve malocclusion repair.